Assessment of Financial Risk in Uncertainty Environments - Martínez Barrio, Juan Carlos (Journal of Accounting and Finance, 2020)
An operational composite indicator to evaluate the estimated recovery probability of an entrepreneur’s loan, or any other business-oriented loans, given by ERP= α(RR) + β(SOA) + γ(COA) – [NCR] – [CI] is presented. The resulted indicator evaluates the recovery probability of an entrepreneur/SME/company loan in uncertainty environments, without guarantees or collaterals. This indicator has been named “Estimated Recovery Probability”, ERP. Being a totally new approach, ERP methodology has been tested in actual scenarios showing its efficiency in comparison with current risk assessment methods used by the traditional financial system, pointing out the fact that guarantees or collaterals have not been requested.